(untitled) (Bangladesh Journal of Pharmacology, 2012)
The antidiarrheal effects of the aqueous leaf extract of C. sesamoides at 25, 50 and 100 mg/kg body weight was evaluated in female rats using gastrointestinal transit, diarrhea and enteropooling induced by castor oil models. The extract was positive for alkaloids, saponins, flavonoids and phenolics. The 25 mg/kg body weight of the extract significantly (p<0.05) prolonged the onset time of diarrhea, decreased the fecal parameters (number, water content, fresh weight, total number of wet feaces) with no episode in the animals treated with 50 and 100 mg/kg body weight. The activity of small intestine Na+-K+ ATPase increased (p<0.05) while the nitric oxide, volume and mass of intestinal fluid as well as the distance travelled by the charcoal meal decreased. The patterns of changes were similar to the reference drugs. Overall, the antidiarrheal activity of the aqueous leaf extract of Ceratotheca sesamoides may be due to alkaloids, phenolics, flavonoids and saponins present in the extract.